Mockingjay - Collins, Suzanne, 1964- (Waterville, ME : Thorndike Press, 2010)
The Capitol is angry that Katniss Everdeen has survived the Hunger Games twice, stirring unrest by having defied the rules, and President Snow has made it clear that she, her family and friends, and the people of District 12 may all be held accountable.
Keywords: Large type books; Insurgency -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Contests -- Juvenile fiction; Insurgency -- Fiction; Survival -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction